Strategi Peningkatan Produksi Perikanan Budidaya Berbasis Teknologi dan Potensi Lokal di Kabupaten Pasuruan: Analisis Implementasi Program dan Efektivitas Sarana Prasarana - herawan, ade (DEMOKRASI, 2025)
This study aims to evaluate the impact of technology implementation, local potential optimization, and the enhancement of performance and accountability of infrastructure on the increase in production and economic value of aquaculture businesses in Pasuruan Regency. The main focus of this research is to assess the effectiveness of programs designed to improve productivity, turnover, and the contribution of the fisheries sector to the Gross Regional Domestic Product (GRDP) of Pasuruan Regency. The research method used is a descriptive analytical approach with a combination of quantitative and qualitative data. Quantitative data was collected through surveys measuring productivity, turnover, and the contribution of the fisheries sector, while qualitative data was obtained through in-depth interviews with fish farmers, fisheries extension workers, and relevant officials. The results of the study show that the application of modern technologies, such as recirculation systems and biofloc, has successfully improved aquaculture productivity. In addition, programs based on local potential have proven effective in increasing aquaculture business turnover, although the growth rate has declined over time. Performance and accountability improvement programs also showed a positive impact on budget efficiency and infrastructure management, supporting the sustainability of this sector. Overall, the aquaculture sector in Pasuruan Regency has experienced significant development, although challenges such as market limitations and natural resource constraints still need to be addressed. This study suggests the importance of synergy between the government, the community, and the private sector to maximize the potential and sustainability of the fisheries sector